HPV and Cancer - Radosevich, James A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
(3z(BHPV and Cancer(3y (Bis a concise read that covers all aspects of the Human Papilloma Virus as it relates to human cancers. While written by professionals, it design to be understandable by those that are not in the field, yet it has the technical details that professionals want to stay abreast of this changing field. The book starts out the history of HPV and progresses into the molecular biology of the virus and our current understand of the structure and functions of the proteins and genes it encodes. We then look at the dynamic trends of this infectious agent in the human population, how it interacts with human cells, and the role it plays with other organisms to produce both benign and malignant tumors. Lastly, there is a discussion about a new vaccine for HPV and the hopes that are held by many to change the trends with this virus and the associated cancers it produces.s
Keywords: Medicine; Oncology; Medical virology; Emerging infectious diseases; Biomedicine; Cancer Research; Biomedicine general; Virology; Oncology; Infectious Diseases